Penerapan Sanksi Kebiri Kimia Bagi Pelaku Tindak Pidana Kekerasan Seksual Anak Dalam Perspektif Hak Asasi Manusia - Sujasmin Sujasmin (Jurnal USM Law Review)
This study aims to analyze the application of chemical castration against perpetrators of child sexual abuse from a human rights (HR) perspective and examine the legal considerations in the District Court Decision of Banjarmasin Number 858/Pid.Sus/2022/PN.Bjm. Child sexual abuse is a serious crime that causes long-term physical and psychological harm. The Indonesian government responded by enacting chemical castration sanctions under Law Number 17 of 2016 and Government Regulation Number 70 of 2020. The research method used is normative juridical with statutory and conceptual approaches, and qualitative analysis of primary and secondary legal materials. The results show that the implementation of chemical castration has the potential to conflict with the principle of non-degrading treatment under international human rights instruments ratified by Indonesia. The novelty of this study lies in its evaluative approach, combining national legal norms, international HR standards, and actual judicial practice. It concludes that chemical castration may be maintained if it meets medical consent, strict supervision, and protects the rights of offenders. The study recommends a policy reform focusing on offender rehabilitation, public education, and independent oversight to ensure comprehensive rights protection.